2015
DOI: 10.20344/amp.6126
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatose Cólica Tratada com Metronidazol e Oxigenoterapia Hiperbárica: Um Caso de Sucesso

Abstract: Acta Med Port 2015 Jul-Aug;28(4):534-537 RESUMOA pneumatose intestinal, caracterizada pela presença de gás na parede do cólon, é uma condição incomum com um espectro de apresentação variável. Pode ser idiopática ou secundária a outras doenças. A tomografia computorizada é o método de diagnóstico com maior sensibilidade. Na ausência de sinais e sintomas sugestivos de complicações, como a perfuração e a peritonite, a pneumatose intestinal pode ser tratada de forma conservadora. Apresenta-se o caso de uma mulher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Antibiotics including metronidazole and quinolone can target intestinal bacteria and reduce hydrogen production. 5 , 27 (3) Oxygen therapy or HBOT could be considered for patients with obvious symptoms but no surgical indications. 3 A patient received HBOT in our study and a follow-up colonoscopy showed lesions became effectively alleviated; (4) endoscopic therapy: the gas inside the cyst can be removed through puncture by fine needle aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics including metronidazole and quinolone can target intestinal bacteria and reduce hydrogen production. 5 , 27 (3) Oxygen therapy or HBOT could be considered for patients with obvious symptoms but no surgical indications. 3 A patient received HBOT in our study and a follow-up colonoscopy showed lesions became effectively alleviated; (4) endoscopic therapy: the gas inside the cyst can be removed through puncture by fine needle aspiration.…”
Section: Discussionmentioning
confidence: 99%